Genome engineering tools for building cellular models of disease. (22nd June 2016) - Lin, Jennie; Musunuru, Kiran
Abstract : With the recent development of methods for genome editing of human pluripotent stem cells, study of the genetic basis of human diseases has been rapidly advancing. Genome‐edited differentiated stem cells have provided new and more accurate insights into genomic underpinnings of diseases for which there have not been adequate treatments, and moving toward clinical application of genome editing holds great promise for acceleration of therapeutic translation. Here, we review recent advances in genome‐editing technologies and their application to human biology in disease modeling and beyond. Abstract : Genome‐editing methods involve the formation of a double‐stranded DNA break followed by a repair strategy resulting in either a knockout or site‐specific mutagenesis. This approach can facilitate the study of gene function in induced pluripotent stem cells (iPSCs) from healthy individuals or individuals with disease mutations. iPSCs can then be differentiated into the cell type of interest for further study.